South China Sea disputes : still no evidence of historical Chinese claims - Hayton, Bill (2014)
Despite China's assertion of its historical claims to parts of the South China Sea, recent arguments by some commentators repeat a number of commonly-held misunderstandings about the South China Sea disputes and does not provide evidence in support of China's claims.